Danger ahead: the burden of diseases, injuries, and risk factors in the Eastern Mediterranean Region, 1990-2015 - El Bcheraoui, Charbel; Jonas, Jost B.; Mokdad, Ali (International journal of public health, 2018)
OBJECTIVES: The Eastern Mediterranean Region faces several health challenges at a difficult time with wars, unrest, and economic change. - METHODS: We used the Global Burden of Disease 2015 study to present the burden of diseases, injuries, and risk factors in the Eastern Mediterranean Region from 1990 to 2015. - RESULTS: Ischemic heart disease was the leading cause of death in the region in 2015, followed by cerebrovascular disease. Changes in total deaths ranged from a reduction of 25% for diarrheal diseases to an increase of about 42% for diabetes and tracheal, bronchus, and lung cancer. Collective violence and legal intervention increased by 850% during the time period. Diet was the leading risk factor for disability-adjusted life years (DALYs) for men compared to maternal malnutrition for females. Childhood undernutrition was the leading risk factor for DALYs in 1990 and 2005, but the second in 2015 after high blood pressure. - CONCLUSIONS: Our study shows that the region is facing several health challenges and calls for global efforts to stabilise the region and to address the current and future burden of disease.